2011
DOI: 10.5530/pj.2011.19.11
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase Inhibitory, Cytotoxicity and Free Radical Scavenging Activities of Selected Medicinal Plants Used in Indian Traditional Medicine

Abstract: Introduction: The enzyme cyclooxygenase (COX) has been implicated to be a key enzyme involved in recruiting inflammations. Developing COX inhibitors has remained one of the important aspects of developing novel and safe antiinflammatory agents. An attempt has made to find the medicinal plants as alternatives to presently available NSAIDs (Non steroidal anti-inflammatory drugs). Methods: In the present study the samples of Enicostema axillare (Lam.) Raynal. [Gentianaceae], Argemone mexicana L. [Papaveraceae], C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…28 , 29 It is evident that several plants have been used in traditional ayurvedic medicine for treatment and management of distinct inflammatory disorders and wound healing activities. 30 There is clear evidence addressing the importance of plant derived COX inhibitors in the management of inflammatory disorders. Baumann and coworkers were the first to report in a study that some dietary polyphenols inhibit arachidonic acid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…28 , 29 It is evident that several plants have been used in traditional ayurvedic medicine for treatment and management of distinct inflammatory disorders and wound healing activities. 30 There is clear evidence addressing the importance of plant derived COX inhibitors in the management of inflammatory disorders. Baumann and coworkers were the first to report in a study that some dietary polyphenols inhibit arachidonic acid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…COX-1 and COX-2. These two isoforms of COX are almost identical in structure but have important differences in substrate and inhibitor selectivity and in their intracellular locations (Gacche et al, 2011). Among these two isoforms, COX-2 involved in mediating the inflammatory process produces PGE 2 from endogenous arachidonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…presented also the major phenolic content ( Figure 2(b) ). In the study of Gacche et al [ 35 ], polar extracts of Vitex negundo showed higher DPPH radical scavenging activity, while the nonpolar extract did not react with this radical. Similar to our results, in hexanic extracts of Vitex mollis , DPPH radical inhibition was very low in both parts of the plant.…”
Section: Resultsmentioning
confidence: 99%